Diagnosing the accretion flow in ultraluminous X-ray sources using soft X-ray atomic features - Middleton, Matthew J.; Walton, Dominic J.; Fabian, Andrew; Roberts, Timothy P.; Heil, Lucy; Pinto, Ciro; Anderson, Gemma; Sutton, Andrew (Monthly Notices of the Royal Astronomical Society, 2015)
The lack of unambiguous detections of atomic features in the X-ray spectra of ultraluminous X-ray sources (ULXs) has proven a hindrance in diagnosing the nature of the accretion flow. The possible association of spectral residuals at soft energies with atomic features seen in absorption and/or emission and potentially broadened by velocity dispersion could therefore hold the key to understanding much about these enigmatic sources. Here we show for the first time that such residuals are seen in several sources and appear extremely similar in shape, implying a common origin. Via simple arguments we assert that emission from extreme colliding winds, absorption in a shell of material associated with the ULX nebula and thermal plasma emission associated with star formation are all highly unlikely to provide an origin. Whilst CCD spectra lack the energy resolution necessary to directly determine the nature of the features (i.e. formed of a complex of narrow lines or intrinsically broad), studying the evolution of the residuals with underlying spectral shape allows for an important, indirect test for their origin. The ULX NGC 1313 X-1 provides the best opportunity to perform such a test due to the dynamic range in spectral hardness provided by archival observations. We show through highly simplified spectral modelling that the strength of the features (in either absorption or emission) appears to anti-correlate with spectral hardness, which would rule out an origin via reflection of a primary continuum and instead supports a picture of atomic transitions in a wind or nearby material associated with such an outflow. ; Comment: 10 pages, 6 figures, accepted to MNRAS